Effective cellular and neutralizing immunity against SARS-CoV-2 after mRNA booster vaccination is associated with pDC and B cell activation - Fabricius, Dorit; Ludwig, Carolin; Proffen, Matthias; Hägele, Janina; Scholz, Judith; Vieweg, Christiane; Rode, Immanuel; Hoffmann, Simone; Körper, Sixten; Schrezenmeier, Hubert; Jahrsdörfer, Bernd (Frontiers in Immunology, 2025)
IntroductionThe emergence of SARS-CoV-2 variants of concern (VOCs), particularly Omicron, has challenged the efficacy of initial COVID-19 vaccination strategies. Booster immunizations, especially with mRNA vaccines, were introduced to enhance and prolong immune protection. However, the underlying mechanisms of humoral and cellular immunity induced by homologous versus heterologous vaccination regimens remain incompletely understood. This study aimed to elucidate the immune responses, including B cell, plasmacytoid dendritic cell (pDC), and T cell activation, following mRNA booster vaccination.MethodsIn a longitudinal cohort study, 136 individuals received three different vaccination regimens: homologous mRNA, heterologous vector-mRNA-mRNA, or heterologous vector-vector-mRNA vaccinations. Serum and peripheral blood mononuclear cells (PBMCs) were collected at multiple time points up to 64 weeks after initial vaccination. Anti-SARS-CoV-2 IgG titers and neutralization capacity against the wildtype virus and Omicron variant were measured using ELISA and cPass assays. Cellular immunity was assessed by IFN-γ release assays, and flow cytometry was employed to analyze B cell and pDC frequencies, viability, and activation markers. Functional pDC-mediated T cell activation was evaluated in mixed lymphocyte cultures.ResultsmRNA booster vaccination stabilized high anti-SARS-CoV-2 IgG titers and neutralizing activity against wildtype virus across all regimens, with the homologous mRNA group showing the highest antibody titers and Omicron neutralization capacity. Peripheral B cell frequencies and activation markers (MHC class I/II, CD86) were significantly upregulated post-booster. pDCs demonstrated enhanced antigen-presenting capacity and significantly promoted SARS-CoV-2-specific T cell IFN-γ responses in vitro. Despite differences in humoral responses between regimens, breakthrough infection rates up to 25 weeks post-booster were comparable across cohorts, suggesting compensatory mechanisms via cellular immunity.DiscussionOur findings highlight the pivotal role of pDCs and T cells in sustaining effective immunity following mRNA booster vaccination. While homologous mRNA regimens induce superior humoral responses, robust cellular immunity in heterologous regimens may balance protection levels against breakthrough infections. The study underscores the importance of integrated humoral and cellular immune responses, suggesting potential for optimized booster strategies and pDC-targeted vaccine designs to enhance long-term protection against SARS-CoV-2 and emerging variants.